Asam Basa Terintegrasi Islam dalam Media Lectora Inspire - Andre Bintang Kurniawan; Kuncoro Hadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Islamic integrated learning media innovations need to be improved so that the chemistry learning process becomes more interesting. This research is expected to produce an integrated Islamic acid-base learning media in Lectora Inspire media that is valid based on the validity of material experts, media experts, teacher practicality tests and student responses and their application in class. The model in this Research and Development (R&D) research is a 4-D model, namely Define, Design, Develop, and Disseminate. The location of the research was conducted at the 10th State Senior High School (SMAN) Pekanbaru. The results of the research in the form of an integrated Islamic acid-base design on Lectora Inspire media were validated by material experts obtained 92.50% with very valid criteria and media experts obtained 92.50% with very valid criteria and Islamic integration experts obtained 72.5% valid criteria. Draft I was revised based on input from experts. In Draft II the practicality test was carried out by chemistry subject teachers with very practical criteria of 95.33%, and student response test results obtained a very attractive score of 87.29%. From this test, Islamic integrated acids and bases in Lectora Inspire media are suitable for use as learning media in the learning process at school. The last stage was socialization to the Pekanbaru City Chemistry MGMP teachers which resulted in a Very Worthy usage rate for other classes of 94.19%.